2018
DOI: 10.7759/cureus.3503
|View full text |Cite
|
Sign up to set email alerts
|

Inhalation of 1-1-difluoroethane: A Rare Cause of Pneumopericardium

Abstract: We report a case of a 32-year-old man with a past medical history of ethanol use disorder who was brought in unresponsive after inhaling six to 10 cans of the computer cleaning product, Dust-Off. After regaining consciousness, he endorsed severe, pleuritic chest and anterior neck pain. Labs were notable for elevated cardiac enzymes, acute kidney injury, and his initial electrocardiogram (ECG) revealed a partial right bundle branch block with a prolonged corrected QT interval (QTc). On chest X-ray as well as ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…The Florida State Medical Examiners Commission found that there were 49 statewide deaths caused by inhalants in 2018 of which 83% involved halogenated inhalants, especially DFE [ 24 ]. Reported acute health effects of DFE inhalation in nonfatal cases include auditory and visual hallucinations and delusions [ 25 ], mania with psychosis [ 26 ], disorientation, poor judgement and disinhibition, tremors, ataxia [ 23 ], generalized tonic clonic seizure activity [ 27 ], dyspnea on exertion [ 23 ], pulmonary irritation and cough [ 28 ], frostbite burns of skin [ 20 , 29 ], cutaneous burn injury by hydrofluoric acid from thermal degradation of DFE [ 30 ], cutaneous flame burns from fire ignition of DFE [ 30 ], angioedema [ 31 ], palpitations and irregular pulse, chest pain, pneumopericardium [ 29 ], cardiomyopathy [ 32 , 33 ], toxic myocarditis [ 23 ], nausea and vomiting, acute liver injury and fulminant hepatitis [ 23 , 33 , 34 ], rhabdomyolysis and acute renal failure [ 22 , 33 , 34 ]. Some reported long-term health effects include skeletal fluorosis [ 35 ] and possibly chronic kidney disease [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…The Florida State Medical Examiners Commission found that there were 49 statewide deaths caused by inhalants in 2018 of which 83% involved halogenated inhalants, especially DFE [ 24 ]. Reported acute health effects of DFE inhalation in nonfatal cases include auditory and visual hallucinations and delusions [ 25 ], mania with psychosis [ 26 ], disorientation, poor judgement and disinhibition, tremors, ataxia [ 23 ], generalized tonic clonic seizure activity [ 27 ], dyspnea on exertion [ 23 ], pulmonary irritation and cough [ 28 ], frostbite burns of skin [ 20 , 29 ], cutaneous burn injury by hydrofluoric acid from thermal degradation of DFE [ 30 ], cutaneous flame burns from fire ignition of DFE [ 30 ], angioedema [ 31 ], palpitations and irregular pulse, chest pain, pneumopericardium [ 29 ], cardiomyopathy [ 32 , 33 ], toxic myocarditis [ 23 ], nausea and vomiting, acute liver injury and fulminant hepatitis [ 23 , 33 , 34 ], rhabdomyolysis and acute renal failure [ 22 , 33 , 34 ]. Some reported long-term health effects include skeletal fluorosis [ 35 ] and possibly chronic kidney disease [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…We also found multiple reports of huffing abuse causing myocarditis, pneumopericardium, rapid airway compromise, and chemical or thermal burns [1,[5][6][7]. Inhalant abuse should be considered as a differential diagnosis in young patients presenting with elevated cardiac, liver, or possibly renal markers of unknown etiology.…”
Section: Discussionmentioning
confidence: 79%